Tensilely Strained Ge Films on Si Substrates Created by Physical Vapor Deposition of Solid Sources. Issue 1 (December 2018) - Li, Yize; Nguyen, John
Abstract The development of Si-compatible active photonic devices is a high priority in computer and modern electronics industry. Ge is compatible with Si and is a promising light emission material. Nearly all Ge-on-Si materials reported so far were grown using toxic precursor gases. Here we demonstrate the creation of Ge films on Si substrates through physical vapor deposition of toxin-free solid Ge sources. Structural characterization indicates that a high tensile strain is introduced in the Ge film during the deposition process. We attribute the presence of such a tensile strain to the difference in thermal expansion coefficient between Si and Ge. A Ge peak, centered at 2100 nm, is evident in the photoluminescence spectra of these materials, which might result from direct band gap photoluminescence alone, or from superposition of direct band gap and indirect band gap photoluminescence. These Ge-on-Si materials are therefore promising in light emission applications.